2011
DOI: 10.1016/j.febslet.2011.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Sobemovirus RNA linked to VPg over a threonine residue

Abstract: Edited by Tamas DalmayKeywords: Southern bean mosaic virus Ryegrass mottle virus RNA linkage Phosphorylation Mass spectrometry Viral protein genome linked Protein RNA covalent bond a b s t r a c t Positive sense ssRNA virus genomes from several genera have a viral protein genome-linked (VPg) attached over a phosphodiester bond to the 5 0 end of the genome. The VPgs of Southern bean mosaic virus (SBMV) and Ryegrass mottle virus (RGMoV) were purified from virions and analyzed by mass spectrometry. SBMV VPg was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…Surprisingly for MNV the corresponding peptide was also detected without the RNA modification suggesting that RNA modification was lost during sample preparation. In addition we detected random aspartate and glutamate ethylation, methionine and tryptophan oxidations (Table 1 and data not shown), which are known to be generated in vitro during sample preparation (Stadtman & Levine, 2003;Xing et al, 2008;Olspert et al, 2011a) and were therefore not considered of biological relevance.…”
Section: Detection Of Fcv and Mnv Vpg Peptides And Post-translationalmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly for MNV the corresponding peptide was also detected without the RNA modification suggesting that RNA modification was lost during sample preparation. In addition we detected random aspartate and glutamate ethylation, methionine and tryptophan oxidations (Table 1 and data not shown), which are known to be generated in vitro during sample preparation (Stadtman & Levine, 2003;Xing et al, 2008;Olspert et al, 2011a) and were therefore not considered of biological relevance.…”
Section: Detection Of Fcv and Mnv Vpg Peptides And Post-translationalmentioning
confidence: 99%
“…2-10 µg of total RNA was used per analysis. The samples were then dried under vacuum, purified with StageTips (Rappsilber, Mann & Ishihama Y, 2007) and analyzed by LC-MS/MS using an Agilent 1200 series nanoflow system (Agilent Technologies) connected to a LTQ Orbitrap massspectrometer (Thermo Electron) equipped with a nanoelectrospray ion source (Proxeon), as described previously (Olspert et al, 2011a). LTQ Orbitrap was operated in the data dependent mode with a full scan in the Orbitrap (mass range m/z 300-1900, resolution 60 000 at m/z 400, target value 1 Â 106 ions) followed by up to five MS/MS scans in the LTQ part of the instrument (normalized collision energy 35%, wideband activation enabled, target value 5000 ions).…”
Section: Mass-spectrometric Analysis Of Fcv and Mnv Vpg-linked Rnamentioning
confidence: 99%
“…The 5′UTR bounds covalently a viral genome-linked protein (VPg). The studies on the VPg-s of RYMV, CfMV, SBMV, and RGMoV identified a species-specific linkage between the 5′ phosphate group of the RNA and the hydroxyl group of the amino acid residue (tyrosine, serine or threonine) at the N-termini of VPg-s [ 58 , 59 ]. The RYMV VPg was shown to interact with eukaryotic translation initiation factor eIF(iso)4G [ 60 , 61 ].…”
Section: Genomic Organizationmentioning
confidence: 99%
“…Such an abnormal migration of VPg, due to post-translational modifications, has also been reported in other members [27], [28] of the genus Sobemovirus . Mass spectrometric analysis of CfMV, RYMV, SBMV and RGMoV VPgs isolated from native virus showed that they were phosphorylated and nucleotidylylated [28], [29]. The Pro-VPg and VPg bands could also be detected in native virus inoculated cotyledon leaf membrane fraction (data not shown).…”
Section: Resultsmentioning
confidence: 94%